Pressure Gauges and Satellite Altimetry Ensure the Continuity of Florida Current Transport Observations - Denis L. Volkov; Ryan H. Smith; Rigoberto F. Garcia (Geophysical Research Letters)
Abstract The Florida Current (FC), the initial segment of the Gulf Stream, is a key component of both the meridional overturning and horizontal gyre circulations in the subtropical North Atlantic. The four‐decade‐long record of the FC volume transport derived from submarine cable measurements constitutes the longest quasi‐continuous climate record of any boundary current. Unfortunately, data collection ceased in November 2023 due to a mechanical failure of the cable. While efforts are underway to restore the cable system, alternative methods for estimating the FC transport are urgently needed. Here, we combine data from a pair of pressure gauges deployed on either side of the FC at 27°N with satellite altimetry to extend daily transport estimates and fill gaps in the cable record. We demonstrate that transport estimates based on cross‐stream pressure differences represent a suitable interim substitute for cable‐based measurements, although they are limited by the vertical incoherence of the flow.